A geodetic matched filter search for slow slip with application to the Mexico subduction zone. Issue 12 (18th December 2017) - Rousset, B.; Campillo, M.; Lasserre, C.; Frank, W. B.; Cotte, N.; Walpersdorf, A.; Socquet, A.; Kostoglodov, V.
Abstract: Since the discovery of slow slip events, many methods have been successfully applied to model obvious transient events in geodetic time series, such as the widely used network strain filter. Independent seismological observations of tremors or low‐frequency earthquakes and repeating earthquakes provide evidence of low‐amplitude slow deformation but do not always coincide with clear occurrences of transient signals in geodetic time series. Here we aim to extract the signal corresponding to slow slips hidden in the noise of GPS time series, without using information from independent data sets. We first build a library of synthetic slow slip event templates by assembling a source function with Green's functions for a discretized fault. We then correlate the templates with postprocessed GPS time series. Once the events have been detected in time, we estimate their duration T and magnitude M w by modeling a weighted stack of GPS time series. An analysis of synthetic time series shows that this method is able to resolve the correct timing, location, T, and M w of events larger than M w 6 in the context of the Mexico subduction zone. Applied on a real data set of 29 GPS time series in the Guerrero area from 2005 to 2014, this technique allows us to detect 28 transient events from M w 6.3 to 7.2 with durations that range from 3 to 39 days. These events have a dominant recurrence time of 40 days and are mainly located at the downdip edges of the M w >7.5 slow slip events. Key Points: We developed a geodetic matched filter that specifically allows for the search of low‐amplitude slow slip events Synthetic tests show that this method is able to resolve M w > 6 events in the context of the Mexico subduction zone The application on real data between 2005 and 2014 enables to detect 28 slow slip events of M w between 6.3 and 7.2 in the Guerrero area